If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 8 + -2y = 26 Reorder the terms: 8 + 5y + -2y = 26 Combine like terms: 5y + -2y = 3y 8 + 3y = 26 Solving 8 + 3y = 26 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3y = 26 + -8 Combine like terms: 8 + -8 = 0 0 + 3y = 26 + -8 3y = 26 + -8 Combine like terms: 26 + -8 = 18 3y = 18 Divide each side by '3'. y = 6 Simplifying y = 6
| 4z^2+2(z^2-3)=0 | | (x+4)(x+4)=(x+4)(x)+(x+4)(2) | | 7x+y+3=y | | 88=125-(-n) | | 4(2k+7)=2(k+2) | | 6x=6x+4 | | (3-y)2=18 | | 9m-(6m+9)=53 | | 7x+y*3=y | | 5+3(Q-4)=2(Q-1) | | x^2-36a^2+6x+9=0 | | -3m+39-9(m-1)=7m-(4m-5)-2m+4 | | 2a+3=0.5(6+4a) | | X^2+2x+40=x^2-x+190 | | x^3-4x+3x^2-12= | | 5x+7x-42=63-9x | | 4=(-0.8n) | | 4x+2=5x-5 | | z-1/4=7/8 | | -7n+-9=-5 | | 40k+80=30k+120 | | 2[d-(2d+14)+11]=2(d+3) | | (21-4)(21+a)=126+1 | | 28=18+5d | | 10a-35=-8a+1 | | x(x)-5x+4=x(x)+3x+52 | | 9(x+y)-3(2x-5y)= | | 25x^3+40x^2-9x=0 | | 2+2x-4=3x+27 | | -4-3x=-6-6 | | X^2+4=x^2+x | | -4d+6=12 |